The Concept of Professional Kafa'ah (Hirfah) in Perspective; Imam Malik, Imam Shafi'i, and The Correlation of The Opinion of Sheikh Muhammad Arsyad Al-Banjari in Kitab An- Nikah - Hallymah Thussadyah Maura Putri; Husna Khatimah; Muhammad Siraji (Legitima : Jurnal Hukum Keluarga Islam, 2023)
Purpose - The researcher will analyze to understand the concept of kafa'ah in work from different perspectives, namely comparing the views of two madzhab imams with different backgrounds and their correlation with the opinion of Sheikh Arshad Al Banjari in Kitab and Nikah. Methods - In this study, the comparative method was used to analyze the viewpoints they expressed regarding the concept of kafa'ah in employment. Findings - In this study, Imam Shafi'i and Sheikh Arshad included profession/hirfah as one of the criteria of kafa'ah, while Imam Malik did not include hirfah as a criterion of kafa'ah because religious equality is the main thing. Thus, this comparative research is expected to provide a more comprehensive insight and understanding of the concept of kafa'ah in employment in the context of Islamic insight. Research implications - Imam Syafi'i places kafa'ah in terms of the profession (hirfah) as prevalent in marriage as well as the opinion of Sheikh Arshad as a scholar of the Syafi'i Madzhab in South Kalimantan, while Imam Malik argues that kafa'ah does not depend on the profession but on one's religion or devotion. Originality/value - The madzhab imams have different views on the criteria for kafa'ah in marriage. Comparing views is interesting because changing times can affect the existence of the law.